Implementing a support mechanism through mentoring for teaching practice by academic teaching staff in the higher education context - Petersen, Lesley K. (Curtin University, 2011)
A growing body of literature on mentoring in higher education is espousing mentoring as an influential mechanism for supporting a teacher‟s academic practice, simultaneously acknowledging that mentoring as a concept and practice is an inherently multi-dimensional phenomenon open to interpretation and critique. Few scholars provide a stipulated definition of mentoring, increasing the likelihood that mentoring will continue to be a topical debate in the educational domain.This study had the dual purpose of investigating the effects of mentoring on an academic teacher‟s practice in the higher education context and the determinants of a mentoring system being implemented within an organisational environment. An extensive literature review exploring mentoring across three disciplines of higher education, health and business highlights a number of significant elements attributed to the transformation of mentoring as a concept into a legitimate mechanism for supporting academic teaching practice.An action research approach guided the collection of data about the influences of mentoring within an organisational context and encompassed four action research cycles of data collection, analysis and reflection. Three distinct participant groups were involved in the study, including five academic teachers who had assumed a mentor role twelve years prior to commencement of the investigation; four mentoring programme coordinators based in higher education institutions within New Zealand and Australia and eighteen practising academic teachers who engaged in dyad mentoring partnerships over a one year period.The findings of the investigation identified a significant link between mentoring and a teacher‟s academic development, influenced by inter-connecting variables at an individual and organisational level. The study culminates in the development of a model for mentoring that proposes a definitive approach for mentoring as a professional development mechanism that supports the teaching practice of teachers in the higher education organisational context, within which the concept, practice and evaluation of mentoring are vehicles for teachers to explore, challenge and change existing paradigms of teaching and learning in higher education.